The Effect of Olive Oil Therapy on Reducing Pruritus in Hemodialysis Patients - Indaryani Indaryani (Jurnal Riset Media Keperawatan, 2026)
Background: Chronic Kidney Failure patients undergoing hemodialysis who experience pruritus are now widely discussed because it turns out this condition is not just a "normal itch," but significantly affects the patient's quality of life, including sleep, stress, depression, and an increased risk of death. This condition is known as CKD-associated pruritus or uremic pruritus. Many patients do not report it because they consider itching to be a "normal" part of dialysis. However, approximately 31–40% of hemodialysis patients experience moderate to severe pruritus. The presence of pruritus requires efforts to improve the problem, one of which is the administration of olive oil therapy, which can reduce the degree of pruritus. The purpose of this study was to determine the application of olive oil therapy to reduce the degree of pruritus in patients undergoing hemodialysis. Method: This research method was quasi-experimental. Sampling was carried out using an accidental sampling technique. Results: Data were analyzed using the Wilcoxon test. The results showed that olive oil therapy had a significant effect on reducing pruritus in patients undergoing hemodialysis (p = 0.001). Conclusion: This study recommends that olive oil therapy be given to help reduce the degree of pruritus so that it can reduce disruption of skin integrity in patients undergoing hemodialysis.